2022
DOI: 10.1002/hpm.3504
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists perception and role in the prevention and management of cardiovascular disease conditions: Evidence from Ghana

Abstract: Background Globally, Cardiovascular Diseases (CVDs) are the leading non‐communicable diseases with a high mortality if not detected and managed early. The study assessed community pharmacists' perception and determined their role in CVDs prevention and management. Method A cross‐sectional study was conducted among 103 registered community pharmacists in the Ahafo, Bono and Bono East regions of Ghana. Data was collected using validated questionnaires through an online and in‐person surveys. The data was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The study indicated that pharmacy professionals’ involvement in CVD prevention and management is generally insufficient, yet there are positive elements, such as patient engagement and lifestyle counseling. Emphasizing the need for enhanced collaboration with healthcare professionals and further training, the study suggests these measures could bolster their contribution to CVD care [ 10 , 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study indicated that pharmacy professionals’ involvement in CVD prevention and management is generally insufficient, yet there are positive elements, such as patient engagement and lifestyle counseling. Emphasizing the need for enhanced collaboration with healthcare professionals and further training, the study suggests these measures could bolster their contribution to CVD care [ 10 , 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survey questionnaire tool was meticulously developed through an iterative process, drawing upon the existing literature [ 10 , 11 , 12 , 13 , 14 , 15 ], the clinical expertise of our research team, and discussions with collaborating CVD researchers from various institutions across Saudi Arabia.…”
Section: Methodsmentioning
confidence: 99%
“…The current study was a questionnaire-based survey. The researchers developed the questionnaire with the help of their extensive prior knowledge in the field and by navigating through existing research literature ( Amadi et al, 2018 , Henneh and Teg-Nefaah Tabong, 2022 ). We performed a pilot investigation to estimate the level of internal consistency and a field pretest was carried out to anticipate the validity of the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…It was a questionnaire-based survey. Elements of the questionnaire were chosen based on the researcher's academic experience and the available literature [12,15]. A 34-item online questionnaire with 3 domains was designed, developed, and validated using the field pretest method and based on the comments, the questionnaire was refined.…”
Section: Study Instrumentmentioning
confidence: 99%
“…Pharmacists are easily and frequently accessible healthcare members in most communities who have a successful role in controlling CVD risk factors [12]. The growing role of pharmacists in health promotion and their knowledge of medicines management, screening patient adherence, and ensuring the prevention and optimal management of diseases such as CVD has been demonstrated in several studies [13][14][15]. In Saudi Arabia, some of the professional bodies, such as 'Saudi Society of Clinical Pharmacy', are conducting continuing medical education programs on the prevention of CVD.…”
Section: Introductionmentioning
confidence: 99%